Expatriate experience as part of the life and career of the expatriate : a cross-cultural adjustment and learning perspective - Puruskainen, Karoliina (2016)
Amidst the ever increasing trend of globalization, expatriation has become of great con-cern. The nature of expatriation is argued to be subject to changes in the external context, organizational structures and careers. Nevertheless expatriates have traditionally been perceived as a fairly homogenous, broad population in the literature and the alternative forms of expatriation besides company-assigned expatriates have received little attention. The purpose of this study is to explore the changing face of expatriation and understand the phenomena of cross-cultural adjustment and learning and their perceived contribution to the overall experience. The study is a qualitative case study and the data was collected by five semi-structured interviews of former or present expatriates with varying backgrounds. The data was analysed by utilizing firstly theme analysis and subsequently narrative analysis. This research approach was selected due to the exploratory and descriptive interest to cover under-researched topics and provide in-depth subjective considerations on the research phenomena. The findings of the study point to increasing heterogeneity in the nature of expatriation as well as a shift beyond the traditional forms of expatriation. There appears to be a subtle shift from companies to individuals and individual career plans as regards the phenomenon. The expatriate experience could be identified to result in considerable professional and personal development. The expatriates were able identify a variety of affective, knowledge, and skill-based learning outcomes, which were typically achieved by practical, people and problem solving oriented learning tactics. Several aspects facilitating adjustment were identified as well.